Molecular Characterization of Vibrio Alginolyticus Isolated From Orbicularia Orbiculata and Corbiculla Moktiana - Mohamed Noor, Noor Rasyila (2007)
Bivalves are prone to bacterial contamination and can be health risk to the consumers. Antibiotic resistance, plasmid profiling and randomly amplified polymorphic DNA analysis (RAPD-PCR) were used to characterize and to detect the clonal relatedness of a total of 60 strains of Vibrio alginolyticus isolated from bivalve (Orbicularia orbiculata) obtained from Tanjung Karang, Selangor, Malaysia and bivalve (Corbiculla moktiana) from Lake Sangkarak, Padang, Indonesia. Antibiotic susceptibility testing to 13 antibiotics showed that all (60) strains were 100% susceptible to gentamicin. All V. alginolyticus isolated from O. orbiculata were 100% resistant to penicillin G. In contrast, there was variability of resistance for C. moktiana isolates towards antibiotic tested. The common resistant patterns for the isolates were resistant to three antibiotics but they did not share the same type of multiple antibiotic resistance. 46.7% and 76.7% of the plasmid occurrence rates were observed among V. alginolyticus isolated from bivalve O. orbiculata (Malaysia) and C. moktiana (Indonesia), respectively. The plasmid sizes ranged between 3.4 to 27.8 kbp with 18 plasmid patterns. A large number of strains (38.3%) were devoid of plasmid but were resistant to penicillin G, nalidixic acid and chloramphenicol. No correlation could be established between the presence of plasmids and antibiotic resistant because many resistant strains were without plasmid. For RAPD-PCR analysis, ten 10-mer primers were screened for both samples and only one primer – primer 3 (Gold - Oligo OPAR 3- 5’ GTGAGGCGCA 3’) showed reproducible and clear banding patterns. Gold-Oligo OPAR 3 produced 59 RAPD patterns. Dendrogram was constructed and analyzed. Four clusters with four untypeable strains were generated. There were similar clones isolated from O. Orbiculata (Malaysia) and C. moktiana (Indonesia) and also clones specific to either O. Orbiculata or C. moktiana. The high level of genomic diversity among these isolates irrespective of geographic origin was confirmed by this technique. It was suggested that strains of V. alginolyticus from both bivalve species were closely related to each other although they were isolated from different geographical areas. The aquatic environment including the bivalves is implicated as the reservoirs for V. alginolyticus and consequently they are responsible for transmission to human. The findings stressed the importance of this bacteria to food safety, public health an even economic.